The Response Regulator SprE (RssB) Is Required for Maintaining Poly(A) Polymerase I-Degradosome Association during Stationary Phase - Carabetta, Valerie J. (American Society for Microbiology (ASM), 2010)
Poly(A) polymerase I (PAP I) is the enzyme responsible for the addition of poly(A) tails onto RNA molecules in Escherichia coli. Polyadenylation is believed to facilitate the destruction of such RNAs by the mRNA degradosome. Recently, it was discovered that the stationary-phase regulatory protein SprE (RssB) has a second function in the control of polyadenylation that is distinct from its known function in the regulated proteolysis of RpoS. In the work presented herein, we used a targeted proteomic approach to further investigate SprE's involvement in the polyadenylation pathway. Specifically, we used cryogenic cell lysis, immunopurifications on magnetic beads, and mass spectrometry to identify interacting partners of PAP I-green fluorescent protein. We provide the first in vivo evidence that PAP I interacts with the mRNA degradosome during both exponential and stationary phases and find that the degradosome can contain up to 10 different proteins under certain conditions. Moreover, we demonstrate that the majority of these PAP I interactions are formed via protein-protein interactions and that SprE plays an important role in the maintenance of the PAP I-degradosome association during stationary phase.